PENYULUHAN HUKUM DAN SOSIALISASI PEMBERDAYAAN MASYAKARAT DI DESA PINOMONTIGA KECAMATAN BULAWA - Nuna, Muten; Tabo, Sarfan; Podungge, Abdul Wahab; Napir, Suaib; Sahi, Nirmala A.; Arsjad, Muh. Fachri; Bilondatu, Agustina; Kodai, Dince A,; Amu, Robby W.; Kasin, Muslim A.; Lamuda, Dessy Pratiwi; Erawan, Moh. Arif; Bilondatu, Nikma; Biongan, Ahiar; Pakaya, Fitriani; Jumriani, Jumriani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2026)
The Legal Counseling and Community Empowerment Socialization Program in Pinomontiga Village, Bulawa District, was part of a student internship program conducted by students of the Faculty of Social and Political Sciences, Universitas Gorontalo, from September 22 to November 5, 2025 at the Activity Management Unit (UPK) of the former PNPM Mandiri Perdesaan. This program aimed to enhance community understanding of legal issues, particularly the new Criminal Code (KUHP), and to provide information on access to free legal aid for underprivileged communities. This study employed a qualitative descriptive method with a participatory approach through direct observation, active involvement, and the implementation of legal counseling activities. The results indicate that the legal counseling program effectively increased community legal awareness, improved understanding of legal rights, and encouraged community empowerment in addressing legal issues independently. In addition, the program was supported by other internship activities, such as improving UPK office facilities and conducting community service activities, which contributed to community development. However, the implementation faced several challenges, including limited time, budget constraints, and insufficient internal coordination. Therefore, it is recommended that future programs be supported by better planning, adequate funding, and improved coordination among stakeholders. Furthermore, continuous and periodic legal counseling programs are necessary to ensure sustainable community empowerment outcomes.